Design of columns subjected to axial compression, nominal and large bending moments using BS 5950:2000 and Eurocode 3 - Heo, Joy Hwee Min. (2011)
The study of the comparison between both codes of practice, British Standards and Eurocode 3 is timely as this is a period where both codes of practice co-exist. It is even more relevant as Singapore is expected to make the crucial switch in Year 2011. Through this final year project, comparisons between the British Standards and Eurocodes can be made.